Effects of behavioural activation on the neural circuit related to intrinsic motivation. Issue 5 (2nd August 2018) - Mori, Asako; Okamoto, Yasumasa; Okada, Go; Takagaki, Koki; Takamura, Masahiro; Jinnin, Ran; Ichikawa, Naho; Yamamura, Takanao; Yokoyama, Satoshi; Shiota, Syouichi; Yoshino, Atsuo; Miyake, Yoshie; et al.
Abstract : Background: Behavioural activation is an efficient treatment for depression and can improve intrinsic motivation. Previous studies have revealed that the frontostriatal circuit is involved in intrinsic motivation; however, there are no data on how behavioural activation affects the frontostriatal circuit. Aims: We aimed to investigate behavioural activation-related changes in the frontostriatal circuit. Method: Fifty-nine individuals with subthreshold depression were randomly assigned to either the intervention or non-intervention group. The intervention group received five weekly behavioural activation sessions. The participants underwent functional magnetic resonance imaging scanning on two separate occasions while performing a stopwatch task based on intrinsic motivation. We investigated changes in neural activity and functional connectivity after behavioural activation. Results: After behavioural activation, the intervention group had increased activation and connectivity in the frontostriatal region compared with the non-intervention group. The increased activation in the right middle frontal gyrus was correlated with an improvement of subjective sensitivity to environmental rewards. Conclusions: Behavioural activation-related changes to the frontostriatal circuit advance our understanding of psychotherapy-induced improvements in the neural basis of intrinsic motivation. Declaration of interest: None.